Effects of acrylic resin monomers on porcine coronary artery reactivity. Issue 10 (2nd July 2016) - Abebe, Worku; West, Daniel; Rueggeberg, Frederick A.; Pashley, David; Mozaffari, Mahmood S.
Abstract: The purpose of the present investigation was to assess the reactivity of porcine coronary arteries under in vitro conditions following their exposure to methyl methacrylate (MMA) and hydroxyethyl methacrylate (HEMA) monomers. Confirming previous studies using rat aortas, both MMA and HEMA induced acute/direct relaxation of coronary ring preparations, which was partly dependent on the endothelium. With prolonged tissue exposure, both monomers caused time- and concentration-dependent inhibition of receptor-mediated contraction of the vascular smooth muscle caused by prostaglandin F2∝ (PGF2∝ ), with HEMA causing more inhibition than MMA. Hydroxyethyl methacrylate, but not MMA, also produced impairment of non-receptor-mediated contraction of the coronary smooth muscle induced by KCl. On the other hand, neither HEMA nor MMA altered relaxation of the smooth muscle produced by the direct-acting pharmacological agent, sodium nitroprusside (SNP). While exposure to HEMA impaired endothelium-dependent vasorelaxation caused by bradykinin (BK), MMA markedly enhanced this endothelial-mediated response of the arteries. The enhanced endothelial response produced by MMA was linked to nitric oxide (NO) release. In conclusion, with prolonged tissue exposure, MMA causes less pronounced effects/adverse consequences on coronary smooth muscle function relative to the effect of HEMA, while enhancing vasorelaxation associated with release of NO from the endothelium. Accordingly, MMA-containing resin materials appear to be safer for human applications than materials containing HEMA.